Cellular Network Densification: A System-Level Analysis With IAB, NCR, and RIS - Gabriel C. M. Da Silva; Victor F. Monteiro; Diego A. Sousa; Darlan C. Moreira; Tarcisio F. Maciel; Fco. Rafael M. Lima; Behrooz Makki (IEEE Access)
As the number of user equipments increases in 5G and beyond, it is desirable to densify the cellular network with auxiliary nodes assisting the base stations. Examples of these nodes include IAB nodes, NCR and RIS. In this context, this work presents a system level overview of these three nodes. Moreover, this work evaluates, through simulations, the impact of network planning aiming at enhancing the performance of a network used to cover an outdoor sport event. We show that, in the considered scenario, in general, IAB nodes provide an improved signal-to-interference-plus-noise ratio and throughput compared to NCR and RIS. However, there are situations where NCR outperforms IAB due to higher level of interference caused by the latter. Finally, we show that the deployment of these nodes in UAV also achieves performance gains due to their aerial mobility. However, UAV constraints related to aerial deployment may prevent these nodes from reaching results as good as those achieved by their stationary deployment.